THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN ENGINEERING (International journal of artificial intelligence, 2026)
Artificial Intelligence (AI) is revolutionizing the engineering industry by enhancing productivity, precision, and innovation. This article explores the growing role of AI in various engineering disciplines, its benefits, challenges, and potential future developments.